Determinasi Kualitas Laporan Dana Desa: Peran Siskeudes, Transparansi, dan Kompetensi Aparatur Desa di Kabupaten Pidie - Rahmaton, Rahmaton; Suparno, Suparno; Amala, Khairun; Yahya, Rizal (Syiah Kuala University Press, 2025)
This study aims to analyze the effect of the use of the Village Financial System (Siskeudes), financial management transparency, and the competence of village officials on the quality of village fund reporting in Pidie Regency. The research population consists of 730 villages in Pidie Regency, with a sample of 88 villages and respondents comprising village treasurers and operators. Primary data were collected through questionnaires and analyzed using multiple linear regression with SPSS version 25. The validity and reliability tests confirmed that the research instruments were valid and reliable, while the classical assumption tests indicated that the regression model was feasible for use. The results show that the use of Siskeudes, financial management transparency, and the competence of village officials have a significant effect, both partially and simultaneously, on the quality of village fund reporting, with a contribution of 61.9%, while the remaining 38.1% is explained by other factors outside the research model. These findings suggest that the integration of information technology through Siskeudes, openness in financial management, and the improvement of village officials competence are key factors in ensuring village fund reporting that is accountable, transparent, timely, and aligned with the principles of good governance.Keyword: Siskeudes; transparency; competence of village officials; reporting quality; village fund